Interação com clientes no desenvolvimento de novos produtos sob a perspectiva da coprodução e da cocriação de valor : uma análise de seu efeito sobre desempenho - Hoeltz, Luciano (2013)
This research aims to understand the possible relationships between co-production and performance in new product development (NPD). Therefore, studies were performed on co-production and NPD in light of the value co-creation, considering research done on the importance of interaction between customers and the firm (PRAHALAD e RAMASWAMY, 2000; 2004; LUSCH e VARGO, 2004; COVA e SALLE, 2008; GUMMESSON e MELE, 2010; CHANDLER e VARGO, 2011; BALLANTYNE et al., 2011; COOPER e EDGETT, 2008; JARUELSKI e DEHOFF, 2011; BONNER, 1999). Based on this understanding, six theoretical propositions were formulated: four of them were focused on the positive effect of the co-production on NPD performance and other two were about organization of the coproduction on NDP process. Interviews with eight NPD experts were done to verify the convergence of these propositions with market practices. Content analysis of the data collected during the interviews revealed convergence of five theoretical propositions, signaling indications that the adoption of the coproduction approach contributes to NPD performance. Finally, this study suggests a research agenda aimed at deepening the theme.